2016
DOI: 10.1002/stem.2275
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CCL15 Mediates Migration of Human Bone Marrow-Derived Mesenchymal Stem Cells Toward Hepatocellular Carcinoma

Abstract: Mesenchymal stem cells (MSCs) possess the ability to migrate toward tumor sites and are regarded as promising gene delivery vehicles for cancer therapeutics. However, the factors that mediate this tropism have yet to be completely elucidated. In this study, through cytokine array analysis, chemokine CCL15 was found to be the most abundant protein differentially expressed in hepatocellular carcinoma (HCC) cell lines compared with a normal liver cell line. Serum CCL15 levels in HCC patients determined by enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Several studies have indicated a crucial role of CCL15 in tumor progression, including HCC, lung cancer, and colorectal cancer . It was reported that mothers against decapentaplegic homolog 4, bound directly to CCL15 gene promoter region to negatively regulate its expression in colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated a crucial role of CCL15 in tumor progression, including HCC, lung cancer, and colorectal cancer . It was reported that mothers against decapentaplegic homolog 4, bound directly to CCL15 gene promoter region to negatively regulate its expression in colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, CCL15 was reported to recruit CCR1 + myeloid–derived suppressor cells and CCR1 + neutrophils to promote metastasis . Meanwhile, CCL15 could also attract a small proportion of bone marrow–derived mesenchymal stem cells toward HCC . Therefore, it appeared that the types of CCR1 + cells were diverse in different tumor microenvironments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [44][45][46] demonstrate the tendency of MSCs to migrate to the sites of the tumor. Therefore, to investigate whether skin MSCs possess the same properties, we simulated the migration of MSCs toward cancer cells (MDA-MB-231) and noncancerous breast epithelial cells (MCF-10A) using Transwell migration assay.…”
Section: In Vitro Migrationmentioning
confidence: 99%
“…Such complexes have been already designed and tested as effective tools for pancreatic cancer. 93 Although we chose breast cancer as a tumor model, recent studies show the applicability of MSC-based therapy for the treatment of tumors of various locations, for example, ovarian, 94 liver, 46 lung, 95 and so on. A considerable amount of research has been done on glioma models, as MSCs are able to cross the blood-brain barrier and localize in intracranial neoplasms.…”
mentioning
confidence: 99%